2004
DOI: 10.1179/000349804x3135
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with participation in a campaign of mass treatment against lymphatic filariasis, in Leogane, Haiti

Abstract: In October 2000, to interrupt transmission of Wuchereria bancrofti, an intense health-education campaign followed by a mass drug administration (MDA) with diethylcarbamazine and albendazole was undertaken in Leogane, Haiti. Three months after the MDA, which was the first in the study area, a knowledge-attitude-practice (KAP) survey, with a cluster-sample design and probability sampling, was undertaken, to determine the existing knowledge of the local residents, their attitudes toward the MDA, and the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 12 publications
3
47
2
Order By: Relevance
“…This percentage is similar to that reported by Mathieu and others for an endemic area in Haiti. 6 Mathieu and others also reported that 36.4% of their study participants knew that mosquitoes transmit the disease. This value was higher in the present study (59.1%).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This percentage is similar to that reported by Mathieu and others for an endemic area in Haiti. 6 Mathieu and others also reported that 36.4% of their study participants knew that mosquitoes transmit the disease. This value was higher in the present study (59.1%).…”
Section: Discussionmentioning
confidence: 87%
“…This finding was statistically significant by univariate and multivariate analysis, and the finding is also consistent with results reported from Haiti. 4,6 In other parts of the world, educational messages related to LF are often transmitted in person, 12 but television seems to have been important for delivering information about LF and MDA in Egypt. This finding supports the decision of the Egyptian MOH to invest heavily in electronic media for publicizing the LF elimination program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in tandem with the findings of Yirga et al, [19] and Nuwaha et al, [24] which positively associated high risk perception with compliance. To address the target communities' knowledge and perception gaps, in Haiti, Mathieu et al, [25] highlighted the importance of knowledge, attitudes, and perception surveys and their influence on behavior, for example, in the participation in public health Programs such as LF elimination. The World Health Organization further recommends that knowledge, attitude, and practice (KAP) surveys be integrated with drug coverage surveys [26] and be utilized to provide valuable information for Program managers, permitting them to adapt health-education messages to changes in public knowledge and attitude, over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, if elimination strategies are to succeed, in-depth socio-cultural understandings of the affected community is pivotal to maintain the sustainability of the program. Earlier studies (Ramaiah et al 2005;Babu and Kar 2004;Mathieu et al 2004) also emphasized that an intensive campaign of information, education, communication and advocacy is necessary if an effective mass drug administration were to be implemented.…”
Section: Discussionmentioning
confidence: 99%